LiFi based automated shopping assistance application in IoT - Akter, Sharmin; Olanrewaju, Rashidah Funke; Islam, Thouhedul, Salma (IOP Publishing, 2018)
Urban people minimize shopping time in daily life due to time constrain. From that point of view, the concept of supermarket is being popular while consumers can buy different items from same place. However, customer spends hours and hours to find desired items in a large supermarket. In addition, it’s also required to be queued during payment at counter that is also time consuming. As a result, a customer has to spend 2-3 hours for shopping in a large superstore. This paper proposes an Internet of Things and Li-Fi based automated application for smart phone and web to find items easily during shopping that can save consumer’s time as well as reduce man power in supermarket.